(untitled) (Bangladesh Journal of Botany, 2010)
Pollen grains of 16 taxa of Allium L. belonging to sections Rhizirideum G. Don ex Koch., Codonoprasum Reichb. and Allium L. were investigated using light and scanning electron microscope, and pollens of four taxa were also examined with transmission electron microscope. Pollens were monosulcate and ellipsoidal. It was observed that the sulcus extends from distal to proximal in all taxa. The exine was semitectate and the tectum was perforate. Columellae were simplicolumellate. Exine sculpture was striate-perforate, striate-rugulate-perforate and rugulate-perforate. A. albidum Fischer ex Bieb. subsp. caucasicum (Regel) Stearn, A. rupicola Boiss ex Mouterde and A. asperiflorum Miscz. were seen to have an operculum. Key words: Allium; Codonoprasum; Rhizirideum; Alliaceae; Pollen morphology; Turkey DOI: 10.3329/bjb.v39i1.5524 Bangladesh J. Bot. 39(1): 37-36, 2010 (June)